Comparative plasma and interstitial fluid pharmacokinetics of flunixin meglumine and ceftiofur hydrochloride following individual and co‐administration in dairy cows. Issue 1 (21st July 2017) - Gorden, P. J.; Kleinhenz, M. D.; Wulf, L. W.; Rajewski, S. J.; Wang, C.; Gehring, R.; Coetzee, J. F.
Abstract : Ceftiofur (CEF) and flunixin meglumine (FLU) are two drugs approved for use in beef and dairy cattle that are frequently used in combination for many diseases. These two drugs are the most commonly used drugs in dairy cattle in their respective drug classes. Two research groups have recently published manuscripts demonstrating altered pharmacokinetics of FLU and CEF in cows affected with naturally occurring mastitis. The objective of this study was to determine whether pharmacokinetics of flunixin meglumine administered intravenously or intramuscularly administered ceftiofur hydrochloride would be altered when co‐administered versus individual administration to healthy dairy cattle. Ten cows were utilized in a three‐period, three‐treatment crossover design, with all cows receiving each treatment one time with a 10‐day washout period between treatments. Following treatment, plasma and interstitial fluid samples were collected and stored for later analysis. Additionally, plasma ultrafiltrate was collected using microcentrifugation to determine plasma protein binding of each drug. Drug concentrations in plasma, plasma ultrafiltrate, and interstitial fluid were determined using high‐pressure liquid chromatography coupled with mass spectrometry. The results of this trial indicate that drug interactions between FLU and CEF do not occur when the two drugs are administered simultaneously in healthy cattle. Further work is needed to determine whether this relationship is maintained in the presence of severe disease.